CeO2 - 10% MOL Gd2O3: efeito da codopagem com X% MOL Sm2O3 (O5 X 52) na microestrutura e na condutividade elétrica - Araújo, Huyrá Estevão de (2011)
Fuel cells are the most promising technology for producing clean energy. In particular, the Solid Oxide Fuel Cell (SOFC) stands out among the various types due to high efficiency at high temperatures (800 ~ 1000°C) resulting in high cost for power generation. The operating temperature decreasing allows the use of non expensive materials and increases cell life time. One of the challenges for reducing the operating temperature is to increase the electrical conductivity of electrolytes. In this context, the ceria-based electrolytes are an alternative due to its high ionic conductivity at intermediate temperatures (500 ~ 650 °C). In this work, commercial powder of 10 mol% Gd2O3 doped Ceria was co-dopped with X% Sm2O3 (0 <X <2.0), using mechanical mixture. Sintering was carried out by conventional method at temperatures of 1400, 1450 and 1500 ° C with 2, 10 and 20 hours of soak time. Relative density above 93% was obtained for all sintering conditions. The grain growth was favored by codopping, specially for samples sintered at 1500 °C - 10 and 20 h, and 1450 °C - 20 h, indicating that in these sintering conditions samarium addition favored the diffusion in the grain boundary region. The highest total electrical conductivity was obtained for 0.5 mol% Sm2O3 sample sintered at 1500 °C-2 h. The values of electrical conductivity for grain and grain boundary, both specific and apparent, didn t achieve the maximum value for the same co-dopped content and the same sintering condition.